Boronic acid derivative activates pyruvate kinase M2 indispensable for redox metabolism in oral cancer cells. (1st March 2022) - Rihan, Mohd; Vineela Nalla, Lakshmi; Dharavath, Anil; Patel, Sagarkumar; Shard, Amit; Khairnar, Amit
Graphical abstract: Highlights: Boronic acid-based Compound 1 activates the tumor pyruvate kinase M2 (PKM2). Activation of PKM2 by Compound 1 hampers the redox balance in oral cancer cells. An link between PKM2 and triose phosphate isomerase 1 (TPI1) is established using PKM2 activator. Compound 1 exhibited excellent PKM2 activation in oral cancer cells with an AC50 value of 25 nM. Abstract: PKM2 is considered a desirable target as its enzymatic activation is expected to cause a diminution in tumorigenesis and prevent limitless replication in cancerous cells. However, considering the functional consequences of kinase inhibitors, the design of PKM2 activators has been an attractive strategy that has yielded potent anticancer molecules like DASA-58. Therefore, a new class of boronic acid derivate was developed to elucidate the possible mechanistic link between PKM2 activation and TPI1 activity, which has a significant role in the redox balance in cancer. The present in vitro study revealed that treatment with boronic acid-based compound 1 and DASA-58 was found to activate PKM2 with an AC50 of 25 nM and 52 nM, respectively. Furthermore, at the AC50 concentration of compound 1, we found a significant increase in TPI1 activity and a decrease in GSH and NADP + /NADPH ratio. We also found increased ROS levels and decreased lactate secretion with treatment. Together with these findings, we can presume that compound 1 affects the redox balance by activating PKM2 and TPI1 activity. Implementation of this treatment strategy may improve the effect of chemotherapy in the conditions of ROS induced cancer drug resistance. This study for the first time supports the link between PKM2 and the TPI1 redox balance pathway in oral cancer. Collectively, the study findings provide a novel molecule for PKM2 activation for the therapeutic intervention in oral cancer.